Understanding the impact, accessibility and diversity of Nordic walking in people with Parkinson's Disease - McCracken, Sarah Jane (2024)
Background Nordic Walking (NW) is an enhanced walking technique that uses special poles to increase the effort of the arms and legs. NW provides an all over body workout that is reported to improve posture and gait, strengthen the back and abdominal muscles, reduce the impact on joints and burn 20% more calories than walking without poles (British Nordic Walking, 2023b). There is a growing body of research supporting the use of NW as a means of regular, outdoor exercise for people of all ages and for those with a range of physical and mental health challenges. Research of NW shows promising outcomes for people with Parkinson’s (PwP), with significant improvements in walking speed and stride length, postural stability, gait, and in cognitive aspects of movement preparation (Ebersbach et al., 2014). However, the effectiveness and results of NW research in this population are inconsistent as there is heterogeneity of participants, various methodologies, no standardised model of NW delivery, and little data about the longer-term physical and psychological implications of NW.